Antioxidant and Anti-Inflammatory Properties of Melatonin in Secondary Traumatic Brain Injury - Mariusz Sieminski; Michalina Reimus; Maria Kałas; Ewelina Stępniewska (Antioxidants)
Traumatic brain injury (TBI) is a disease resulting from external physical forces acting against the head, leading to transient or chronic damage to brain tissue. Primary brain injury is an immediate and, therefore, rather irreversible effect of trauma, while secondary brain injury results from a complex cascade of pathological processes, among which oxidative stress and neuroinflammation are the most prominent. As TBI is a significant cause of mortality and chronic disability, with high social costs all over the world, any form of therapy that may mitigate trauma-evoked brain damage is desirable. Melatonin, a sleep–wake-cycle-regulating neurohormone, exerts strong antioxidant and anti-inflammatory effects and is well tolerated when used as a drug. Due to these properties, it is very reasonable to consider melatonin as a potential therapeutic molecule for TBI treatment. This review summarizes data from in vitro studies, animal models, and clinical trials that focus on the usage of melatonin in TBI.